Peranan Motivasi Prososial dalam Memediasi Pengaruh Motivasi Teori Penentuan Nasib Sendiri terhadap Berbagi Pengetahuan - Saputra, Arco; Bastian, Adolf; Handayani, Ririn (CV. ITTC INDONESIA, 2024)
This study uses a quantitative method with a descriptive and explanatory survey approach. The study was conducted at the Kampar Regency Land Office, with the aim of testing the role of prosocial motivation in mediating the influence of motivation based on self-determination theory on knowledge sharing. The population of this study consisted of all employees of the Kampar Regency Land Office, with a total of 144 people. Based on this population size, according to the Krejcie and Morgan (1970) table, the sample size for this study was 103 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The results of the study indicate that self-determination motivation does not have a significant effect on knowledge sharing, self-determination motivation has a significant positive effect on prosocial motivation, prosocial motivation has a significant positive effect on knowledge sharing, and prosocial motivation mediates a significant positive effect of self-determination motivation on knowledge sharing.